2020
DOI: 10.1155/2020/7573689
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three lncRNAs as Potential Predictive Biomarkers of Lung Adenocarcinoma

Abstract: Background. Lung cancer is the most common cancer and the most common cause of cancer-related death worldwide. However, the molecular mechanism of its development is unclear. It is imperative to identify more novel biomarkers. Methods. Two datasets (GSE70880 and GSE113852) were downloaded from the Gene Expression Omnibus (GEO) database and used to identify the differentially expressed genes (DEGs) between lung cancer tissues and normal tissues. Then, we constructed a competing endogenous RNA (ceRNA) network an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
3
21
0
1
Order By: Relevance
“…These backgrounds suggest the possibility that lncRNAs may be involved in paracrine signaling or cell-to-cell crosstalk. Our findings indicate that LINC01234 downregulation could suppress hepatic carcinoma cell proliferation and induce apoptosis, which is consistent with earlier reports indicating that lncRNAs regulate the progression of liver cancer (23,24). These findings suggest that LINC01234 likely acts to promote tumorigenesis of liver cancer, particularly during the advanced stages of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…These backgrounds suggest the possibility that lncRNAs may be involved in paracrine signaling or cell-to-cell crosstalk. Our findings indicate that LINC01234 downregulation could suppress hepatic carcinoma cell proliferation and induce apoptosis, which is consistent with earlier reports indicating that lncRNAs regulate the progression of liver cancer (23,24). These findings suggest that LINC01234 likely acts to promote tumorigenesis of liver cancer, particularly during the advanced stages of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…These backgrounds suggest the possibility that lncRNAs may be involved in paracrine signaling or cell-to-cell crosstalk. Our ndings indicate that LINC01234 downregulation could suppress hepatic carcinoma cell proliferation and induce apoptosis, which is consistent with earlier reports indicating that lncRNAs regulate the progression of liver cancer (23,24). These ndings suggest that LINC01234 likely acts to promote tumorigenesis of liver cancer, particularly during the advanced stages of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, overexpressed AURKA might promote hepatocellular carcinoma cell growth, adhesion and migration in vitro (28). RACGAP1 has been identified as a hub gene and significantly associated with overall survival in patients with various cancer types, such as pancreatic ductal adenocarcinoma (29), gastric cancer (30), cervical cancer (31) and lung adenocarcinoma (32). Furthermore, Zhao has found that depletion of RACGAP1 could lead to mitotic catastrophe and massive cell death in esophageal squamous cell carcinoma (33).…”
Section: Discussionmentioning
confidence: 99%